Experimental methods in building acoustics for evaluating the flanking transmission - Andrade, Carlos A.R. (2003)
All the scientific work must have at the beginning presupposes and assumptions clarified, that could lead to an objective more easily to accomplish. In this line of thought, the present work is to achieve and clarify those presupposes and assumptions. The design of building and his constructions techniques must be built in such a way that the noise perceived by the occupants is kept down to a level that will not threaten their health and satisfactory living conditions. The acoustical comfort is nowadays one of the main issues for the satisfaction and integration on the society. This has more relevance in developed countries. There are many places where the normal human living is developed: home, work, leaser places, etc, has there are many forms of sound power that disturb those places. However, where the sound perturbation must not reach intolerable levels (acoustical comfort) are in buildings, especially in living buildings. Nowadays is known that sound could be transmitted by structural vibration or by other paths than the separating element of the dwellings. These paths could increase the sound levels of the adjoining rooms with a bigger importance than the supposed a few years ago. The present and future works are more a contribution to obtain better acoustical conditions in buildings and put to the scientific community more knowledge and “savoir faire”. Firstly a search was made in reviews, books and papers specialized in the areas of knowledge of building acoustics and flanking transmission. The information recovered was treated to clarify all the present work done till the moment and to put us in the center of the issue. Secondly several measurements were performed in an old building of the university (in situ measures), by pressure method and intensity method. Those measures were then treated, processed, compared and finally discussed to accomplish the main objective of this work, which is getting an objective theme to the future doctoral thesis.